A Municipal Service Center – For What and For Whom? Understanding the political nature of public administration reform - Kristianssen, Ann-Catrin; Olsson, Jan (Scandinavian Journal of Public Administration, 2016)
Organizational reforms in public administration have been high on the agenda for decades. A popular type is the Municipal Service Center (MSC) gathering citizen-local government interaction in one location, physically and virtually. By using a processual approach, this article reveals the trade-offs and value-priorities made in the process of establishing a MSC in a mid-sized Swedish municipality. The empirical data comprise documents and 29 semi-structured interviews with politicians, managing directors, and other key actors. We discern four key trade-offs: open process of change or final product, efficiency or democracy values, politicians or administrators as key actors, and citizens as customers or co-creators. The article also discusses the trade-offs in relation to broader public administration perspectives. The results indicate that the process was characterized by a view of citizens as service-recipients and customers, a focus on efficiency and the final product, and finally pushed forward by administrators. Most, but no all trade-offs and value-priorities were aligned with new public management (NPM), while other public administration perspectives were not applicabel as expected in a citizen-centred reform process.